2010
DOI: 10.14742/ajet.1089
|View full text |Cite
|
Sign up to set email alerts
|

How do students use podcasts to support learning?

Abstract: Podcasting is used commonly recreationally and is now increasingly used in education. The technology for podcasting is readily available, easy to use and inexpensive, making it an attractive option for providing additional flexible learning resources for students. However, little is known about how podcasts are used by students and the implications for learning. This paper describes how podcasts were used by students in a medical radiation program. In common with many other health science programs, the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 16 publications
(16 reference statements)
5
58
0
1
Order By: Relevance
“…The recordings may, therefore, be a safety net for missed lectures. In this way our findings are consistent with Gysbers et al [32] and Scutter et al [33] who found that students do not generally substitute lectures with recordings but use the recordings for review or to revisit difficult concepts. In addition, Larkin [27] and Gysbers et al [32] reported that students ''expressed a preference for not using recorded lectures to replace face-to-face teaching'' [27, p. 243], which correlates with our students who expressed a strong view that university teaching should not move away from face-to-face teaching.…”
Section: Availability Of Online Materialssupporting
confidence: 93%
“…The recordings may, therefore, be a safety net for missed lectures. In this way our findings are consistent with Gysbers et al [32] and Scutter et al [33] who found that students do not generally substitute lectures with recordings but use the recordings for review or to revisit difficult concepts. In addition, Larkin [27] and Gysbers et al [32] reported that students ''expressed a preference for not using recorded lectures to replace face-to-face teaching'' [27, p. 243], which correlates with our students who expressed a strong view that university teaching should not move away from face-to-face teaching.…”
Section: Availability Of Online Materialssupporting
confidence: 93%
“…Students' views were partially consistent with this in that they described using podcasts when they needed to 'get knowledge into their heads' ). The opportunity to re-listen to a lecture and to take additional notes also appears to facilitate a transition mode of delivery in learning (Forbes, 2008;Scutter, Stupans, Sawyer & King, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of lecture podcasts gives students a chance to listen to a lecture for the first time if they missed a class or to listen to a lecture that they attended in person additional times after the class session is over (Evans 2008;Hew 2009;McCombs and Liu 2007). In others surveys, students reported that they could learn more by hearing the lectures again (Scutter et al 2010) or that the podcasts helped them to better understand the topics of the lecture (Toppin 2011).…”
Section: Learning and Achievement In Face-to-face Lectures And With Lmentioning
confidence: 99%